Co‐infections and transmission dynamics in a tick‐borne bacterium community exposed to songbirds - Heylen, Dieter; Fonville, Manoj; Leeuwen, Arieke Docters; Sprong, Hein (Environmental microbiology, 2016)
We investigated the transmission dynamics of a community of tick‐borne pathogenic bacteria in a common European songbird (Parus major). Tick‐naïve birds were infested with three successive batches (spaced 5 days apart) of field‐collected Ixodes ricinus nymphs, carrying the following tick‐borne bacteria: Rickettsia helvetica (16.9%), Borrelia garinii (1.9%), Borrelia miyamotoi (1.6%), Anaplasma phagocytophilum (1.2%) and Candidatus Neoehrlichia mikurensis (0.4%). Fed ticks were screened for the pathogens after moulting to the next developmental phase. We found evidence for early transmission (within 2.75 days after exposure) of R. helvetica and B. garinii, and to a lesser extent of A. phagocytophilum based on the increased infection rates of ticks during the first infestation. The proportion of ticks infected with R. helvetica remained constant over the three infestations. In contrast, the infection rate of B. garinii in the ticks increased over the three infestations, indicating a more gradual development of host tissue infection. No interactions were found among the different bacterium species during transmission. Birds did not transmit or amplify the other bacterial species. We show that individual birds can transmit several pathogenic bacterium species at the same time using different mechanisms, and that the transmission facilitation by birds increases the frequency of co‐infections in ticks.